Cabozantinib beyond progression improves survival in advanced renal cell carcinoma patients: the CABEYOND study (Meet-URO 21). Issue 1 (2nd January 2022) - Mennitto, Alessia; Zattarin, Emma; Di Maio, Massimo; Bimbatti, Davide; De Giorgi, Ugo; Buti, Sebastiano; Santini, Daniele; Casadei, Chiara; Sorarù, Mariella; Messina, Carlo; Mucciarini, Claudia; Di Lorenzo, Giuseppe; et al.
ABSTRACT: Background: Cabozantinib improves survival in metastatic renal cell carcinoma (mRCC) after prior antiangiogenics. The best treatment at disease progression (PD) is unknown. Being also a AXL/MET inhibitor, involved in acquired resistance, we hypothesized a prolonged tumor growth control in patients continuing cabozantinib despite PD. Research Design and Methods: This retrospective multicenter study enrolled patients receiving cabozantinib after the first line between 2014 and 2020. We compared patients maintaining cabozantinib after first PD due to clinical benefit and good tolerability with those who changed therapy. The postprogression survival (PPS) of both was our primary endpoint. Results: We analyzed 89 patients: 45 received cabozantinib beyond PD and 44 switched therapy. 40.4%, 31.5%, and 28.1% of patients received 1, 2, or >2 prior treatment, respectively. 84.3% were intermediate-poor International Metastatic Renal Cell Carcinoma Database risk. Patients continuing cabozantinib showed a higher response rate to cabozantinib before PD (46.7% vs 25%, p = 0.03) and were more heavily pretreated. Continuing cabozantinib showed a significantly longer PPS compared with switching therapy (median PPS 16.9 vs 13.2 months, HR 0.66, 95%CI 0.48–0.92, p = 0.011). Conclusions: We observed longer PPS in patients continuing cabozantinib beyond PD, suggesting that this could be an effective option.